Antioxidant Defenses in the Human Eye: A Focus on Metallothioneins - Ana Álvarez-Barrios; Lydia Álvarez; Montserrat García; Enol Artime; Rosario Pereiro; Héctor González-Iglesias (MDPI AG, 2021)
The human eye, the highly specialized organ of vision, is greatly influenced by oxidants of endogenous and exogenous origin. Oxidative stress affects all structures of the human eye with special emphasis on the ocular surface, the lens, the retina and its retinal pigment epithelium, which are considered natural barriers of antioxidant protection, contributing to the onset and/or progression of eye diseases. These ocular structures contain a complex antioxidant defense system slightly different along the eye depending on cell tissue. In addition to widely studied enzymatic antioxidants, including superoxide dismutase, glutathione peroxidase, catalase, peroxiredoxins and selenoproteins, inter alia, metallothioneins (MTs) are considered antioxidant proteins of growing interest with further cell-mediated functions. This family of cysteine rich and low molecular mass proteins captures and neutralizes free radicals in a redox-dependent mechanism involving zinc binding and release. The state of the art of MTs, including the isoforms classification, the main functions described to date, the Zn-MT redox cycle as antioxidant defense system, and the antioxidant activity of Zn-MTs in the ocular surface, lens, retina and its retinal pigment epithelium, dependent on the number of occupied zinc-binding sites, will be comprehensively reviewed.